A tobacco-free world: a call to action to phase out the sale of tobacco products by 2040. Issue 9972 (14th March 2015) - Beaglehole, Robert; Bonita, Ruth; Yach, Derek; Mackay, Judith; Reddy, K Srinath
Summary: The time has come for the world to acknowledge the unacceptability of the damage being done by the tobacco industry and work towards a world essentially free from the sale (legal and illegal) of tobacco products. A tobacco-free world by 2040, where less than 5% of the world's adult population use tobacco, is socially desirable, technically feasible, and could become politically practical. Three possible ways forward exist: so-called business-as-usual, with most countries steadily implementing the WHO Framework Convention on Tobacco Control (FCTC) provisions; accelerated implementation of the FCTC by all countries; and a so-called turbo-charged approach that complements FCTC actions with strengthened UN leadership, full engagement of all sectors, and increased investment in tobacco control. Only the turbo-charged approach will achieve a tobacco-free world by 2040 where tobacco is out of sight, out of mind, and out of fashion—yet not prohibited. The first and most urgent priority is the inclusion of an ambitious tobacco target in the post-2015 sustainable development health goal. The second priority is accelerated implementation of the FCTC policies in all countries, with full engagement from all sectors including the private sector—from workplaces to pharmacies—and with increased national and global investment. The third priority is an amendment of the FCTC to include an ambitious global tobacco reduction goal. The fourth priority is a UN high-level meeting on tobacco use to galvanise global action towards the 2040 tobacco-free world goal on the basis of new strategies, new resources, and new players. Decisive and strategic action on this bold vision will prevent hundreds of millions of unnecessary deaths during the remainder of this century and safeguard future generations from the ravages of tobacco use.